Hubungan Komunikasi Terapeutik Perawat Dengan Tingkat Kecemasan Keluarga Pasien Anak Yang Dirawat Diruang PICU RSP Persahabatan: The Relationship Between Nurses' Therapeutic Communication and the Level of Anxiety of the Families of Child Patients Treated in the PICU Room of RSP Persahabatan - Nur, Artha Meulia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: Anxiety is an attitude of discomfort in a person that can be influenced by the attitude and communication style of health workers. Improving one's physical, mental, and emotional health is the primary goal of therapeutic communication, an essential part of nursing. In order to help their clients reach their goals, nurses use a variety of therapeutic communication approaches. (Mersha et al 2023) The results of interviews with 6 parents of children treated in the PICU of Persahabatan Hospital said that the lack of communication by health workers, including nurses, when taking action made families anxious about the condition of their children because usually parents know about their child's condition and the medical devices installed in their children such as IVline when the family asks the nurse on duty during visiting hours. Methods: Descriptive analytical conduct research using a cross-sectional methodology. This research surveyed 35 families whose children under the age of 12 received treatment in the paediatric intensive care unit (PICU) at RSP Persahabatan. Family members' anxiety levels are the dependent variable, whereas therapeutic communication is the independent variable. Data testing on the SPSS application with Univariate and Bivariate analysis. After the data is collected, the accuracy of the data obtained from the collected data is re-checked. The data that has been tabulated is then tested statistically using a computerized Spearman Rho test by comparing the significance value with α = 0,05 (level of significance). If the significance value < α is stated that the statistical test is meaningful, namely there is a relationship. And knowing the correlation coefficient value to find out how strong the relationship is between variables and the nature of the relationship, whether it is inversely proportional or directly proportional. Results: The study obtained data from 35 respondents with the majority of demographic characteristics as follows; 74,3% of respondents were aged 25-35 years; 91,4% were female; 48,6% worked as private employees; 48,6% were high school graduates, 88,6% had never been treated in the PICU 54.3% of respondents said that nurse communication in the PICU was very good and 48,6% of respondents said they had mild anxiety. Since the p-value was less than 0.05, the null hypothesis (H0) was rejected based on the significance value of 0,001 derived from the Spearmen's Rho statistical test analysis. It follows that the degree to which the patient's loved ones worry is related to the efficacy of the nurse's therapeutic communication. The strength of the relationship between nurse therapeutic communication and the level of anxiety experienced by the patient's family is strongly correlated (0,620) suggesting a positive relationship. This suggests that as the nurse's communication skills improve, she gains a better understanding of the patient's family, which in turn reduces their anxiety. On the other side, anxiety levels tend to rise in tandem with poor communication. Discussion: Family members of paediatric patients seen in the PICU Room at RSP Persahabatan report higher levels of anxiety when nurses use therapeutic communication. There is an exact relationship. As a result, the patient's loved ones will feel less worried if the nurse is able to communicate with them effectively is better. Conversely, the worse the communication the worse the level of anxiety.